Peer assessment using one-to-one tablets to improve the English oral presentation of fourth-grade students in Taiwan - Yi-Shan Kuo; Sandy I Ching Wang; Eric Zhi Feng Liu (Computers and Education Open)
The study investigates how peer assessment through individual tablets affects the English language skills of fourth-grade students in Taiwan. It explores the influence of this method on students’ motivation, self-esteem, and academic performance, with the backing of a government push for digital education. By combining quantitative analysis and qualitative interviews, the research delves into the effects of peer assessment through correlation and content analysis. This mixed-method approach aims to provide a thorough understanding of how incorporating digital tools with peer assessment can improve learning outcomes within a structured schooling.